PEMBERDAYAAN IBU RUMAH TANGGA MELALUI PENGOLAHAN DAUN KOPI MENJADI KOPI KAWA DI DESA HARJOMULYO KECAMATAN SILO KABUPATEN JEMBER - Nur Rizki A’yunillah; Pudjo Suharso (Economic Education, University of Jember, 2015)
This is an action research which is done by housewives empowering as labors in plantation. This research is conducted to enrich the skills and knowledge. The attempt in empowering the housewives is done by observing natural resources around their environment, especially the resource which has not been used optimally such as wasted coffee leaves from wiwilan. Training is given to the housewives as the attempt of empowering, such as processing of coffee leaves into Kawa coffee. It is a kind of tea from coffee leaves. Besides to enrich skill, knowledge, and to give productive alternative activity, this training also produces kawa coffee that can enrich the kinds of beverages and decrease the cost to buy coffee and tea. The data collection method which is used in this research is observation, documents, interview, Rural Rapid Appraisal (RRA) and Focus Group Discussion (FGD). Whereas the data analysis is described in the form of narration and then it is displayed in result analysis.